Equivalence of UK nitrogen dioxide diffusion tube data to the EU reference method. (1st October 2021) - Butterfield, David; Martin, Nicholas A.; Coppin, Georgie; Fryer, David E.
Abstract: The UK Government's Department for Environment, Food and Rural Affairs has set up a framework for Local Air Quality Management (LAQM) and Local Authorities widely use nitrogen dioxide (NO2 ) diffusion tubes for Indicative monitoring to calculate annual NO2 concentrations for Review and Assessment purposes. The European Union under directive 20/50/EC on ambient air quality and cleaner air for Europe provides data quality objectives both for Indicative and Fixed measurements of NO2 . LAQM diffusion tube measurements across the UK between 2015 & 2019 were analysed to see if they had been providing data of sufficient quality to be classed as Indicative measurements in support of Local Air Quality Management. Bias corrected annual averaged measurements delivered uncertainties compared to the reference method of <±25%, therefore demonstrating that application of the National bias adjustment factors are providing valid Indicative diffusion tube measurements for the UK. For the full calendar year 2020, the equivalence of the monthly UK Urban NO2 Network (UUNN) diffusion tubes were analysed. The UUNN style diffusion tube is similar to the LAQM style but with the addition of an amorphous polyethylene (PE) filter across the open end of the tube. Results showed that the Network meets the EU Directive uncertainty requirement for Fixed measurements (±15%), without the need for slope or intercept correction. Mean NO2 concentrations derived from triplicate UUNN tubes show a much better precision than the triplicate conventional LAQM tubes. A field determination of the diffusive sampling rate for UUNN tubes was performed at London Marylebone Road, showing that the sampling rate in real world conditions was very similar to that determined in the laboratory. Diffusion tube data form Belgium and Germany were also analysed for equivalence with the Standard Reference Method to help put the UK results into context. Highlights: LAQM diffusion tube results suitable for Indicative measurements (<±25%)according to EU Directive 20/50/EC. UUNN diffusion tube results suitable for Fixed measurements (<±15%) according to EU Directive 20/50/EC. UUNN diffusion tubes showing better measurement precision than conventional LAQM style tubes. Time * concentration thresholds defined for open ended and filter terminated style diffusion tubes. Comparison of UK and EU Member State diffusion tube results.